In vivo assessment of the effect of gel containing lactic acid and glycogen on vaginal microbiota and pH of asymptomatic women of reproductive age - Campaner, Adriana Bittencourt; Rosário Sica, Ana Carolina Alves; d’ Avila Curi, Flavia Salomão; Marchetti, Giulia; Dias, Grazielle Suhett; Teixeira, Bianca Luise (PloS one, 2025)
Background Vaginal dysbiosis is considered a risk factor for the development of gynecological and obstetric complications. This study aimed to evaluate the effects of vaginal gel containing lactic acid on vaginal pH, microbiota composition, and Candida species in asymptomatic women of reproductive age. Methods: 55 menstruating women, with no gynecological complaints, participated in the study, using a gel containing lactic acid twice a week, for 8 weeks. Assessments were conducted before and after the intervention, including measurements of vaginal pH, Nugent score, vaginal microbiota characteristics (alpha diversity index and Community State Types [CSTs] classification), and identification of Candida species. Results: At baseline, 36.4% of women exhibited CST type IV vaginal microbiota, followed by CST type III (30.9%), with vaginal pH values ranging from 4 to 5. After the intervention, there was a significant reduction in vaginal pH (p = 0.0057) and Nugent scores (p = 0.0047). Furthermore, a statistically significant decline was observed in the prevalence of unfavorable taxonomic groups, including Prevotella amnii and Bacterial Vaginosis Associated Bacterium 1, while vaginal lactobacilli remained unaffected. Despite these positive changes, the intervention did not result in a statistically significant alteration in microbial diversity or CST composition (p = 0.12). The gel was well-tolerated, with a low incidence of mild adverse effects reported. Conclusions: The lactic acid-containing gel demonstrated a significant reduction in vaginal pH and Nugent scores in asymptomatic women, indicating possible improvement in vaginal health, that needs to be confirmed in a placebo-controlled study. Although the intervention did not influence microbial diversity and the type of vaginal microbiota at the end of the study, it was able to reduce the prevalence of some taxonomic groups after intervention with the vaginal gel.